Application value of biofluid-based biomarkers for the diagnosis and treatment of spinal cord injury - Wang, Hong-Da; Wei, Zhi-Jian; Li, Jun-Jin; Feng, Shi-Qing (Neural regeneration research, 2022)
Recent studies in patients with spinal cord injuries (SCIs) have confirmed the diagnostic potential of biofluid-based biomarkers, as a topic of increasing interest in relation to SCI diagnosis and treatment. This paper reviews the research progress and application prospects of recently identified SCI-related biomarkers. Many structural proteins, such as glial fibrillary acidic protein, S100-β, ubiquitin carboxy-terminal hydrolase-L1, neurofilament light, and tau protein were correlated with the diagnosis, American Spinal Injury Association Impairment Scale, and prognosis of SCI to different degrees. Inflammatory factors, including interleukin-6, interleukin-8, and tumor necrosis factor α, are also good biomarkers for the diagnosis of acute and chronic SCI, while non-coding RNAs (microRNAs and long non-coding RNAs) also show diagnostic potential for SCI. Trace elements (Mg, Se, Cu, Zn) have been shown to be related to motor recovery and can predict motor function after SCI, while humoral markers can reflect the pathophysiological changes after SCI. These factors have the advantages of low cost, convenient sampling, and ease of dynamic tracking, but are also associated with disadvantages, including diverse influencing factors and complex level changes. Although various proteins have been verified as potential biomarkers for SCI, more convincing evidence from large clinical and prospective studies is thus required to identify the most valuable diagnostic and prognostic biomarkers for SCI.